The histomorphological findings of kidneys after application of high dose and high-energy shock wave lithotripsy - BOZKURT, SÜHEYLA (POLISH UROLOGICAL ASSOC, 2015)
Introduction In this animal study, we reviewed the histomorphological findings in rabbit kidneys after a high number of high-energy shock wave applications and observed if there were any cumulative effects after repeated sessions. Material and methods We formed 2 groups, each consisting of 8 rabbits. Group 1 received 1 session and group 2 received 3 sessions of ESWL with a 7 day interval between sessions, consisting of 3500 beats to the left kidney and 5500 beats to the right kidney per session. The specimens of kidneys were examined histomorphologically after bilateral nephrectomy was performed. For statistical analysis, 4 groups of specimens were formed. The first and second groups received 1 session, 3500 and 5500 beats, respectively. The third and fourth groups received 3 sessions, at 3500 and 5500 beats per each session, respectively. The sections were evaluated under a light microscope to determine subcapsular thickening; subcapsular, intratubular and parenchymal hemorrhage; subcapsular, intersitital, perivascular and proximal ureteral fibrosis; paranchymal necrosis; tubular epithelial vacuolization; tubular atrophy; glomerular destruction and calcification. Results In histopathological examinations capsular thickening, subcapsular hematoma, tubuloepithelial vacuolisation, glomerular destruction, parenchymal hemorrhage, interstitial fibrosis, and perivascular fibrosis were observed in all groups. In statistical analysis, on the basis of perivascular fibrosis and tubular atrophy, there was a beats per session dependent increase of both. Conclusions The detrimental effects from ESWL are dose dependent but not cumulative for up to 3 sessions. Histopathological experimental animal studies will aid in understanding local and maybe, by means of these local effects, systemic effects.
Keywords: ESWL (extracorporeal shock wave lithotripsy); high-energy shock waves; histopathology; kidney; RABBIT KIDNEY; RENAL INJURY; DAMAGE; MODEL; ESWL